PERANCANGAN MEDIA PROMOSI OBJEK WISATA AIR TERJUN MADAKARIPURA GUNA MENINGKATKAN BRAND AWARENESS - Priyatmanto, Baharuddin Adam; Fianto, Achmad Yanu Alif; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: Madakaripura Waterfall is the highest waterfall tourist attraction on the Java Island, with the altitude reaches 200 meters. This waterfal is located on the Probolinggo district, and is still in the tourist area of Bromo-Tengger-Soemeru. Madakaripura Waterfall is managed by the Government Department of culture and tourism of Probolinggo district. This waterfall having the different characteristics with a waterfalls in general, circular shape and resembling a tube with the higher cliffs around the waterfall. This Waterfall also has a strong historical value, because according to legend that circulated in the local area, was formerly believed on a Madakaripura Waterfall be a place of asceticism by Gajah Mada Prime Minister, namely the commander of The Majapahit Kingdom. Madakaripura Waterfall is also used for Yadnya Kasada rituals, namely the traditional rituals taking holy water by the tribe of Tengger Which is celebrated on the 15th full moon day in Kasada month. This tourism area is still considered natural with a fairly challenging terrain, the visitors must walk so far about 2 km, with down the rivers to the location of a waterfall. Madakaripura Waterfall is on the lowest ranks of the numbers tourist visiting in 2012, among other attractions onÂ  Probolinggo district. It is influenced by the promotional media less, therefore needs to be done of promotional media design in accordance with the characteristics and natural potential owned by Madakaripura Waterfall. Expected by the presence of promotion media design for Madakaripura Waterfall attraction, can increase brand awareness and the numbers of tourist visiting in Madakaripura Waterfall.Â Keywords: Design, Promotional Media, Madakaripura Waterfall, Brand Awareness.